Effects of enhanced wind erosion on surface soil texture and characteristics of windblown sediments - Li, Junran; Okin, Gregory S.; Epstein, Howard E. (Journal of Geophysical Research. G. Biogeosciences, 2009)
It is well documented that wind redistributes and transports soil resources in semiarid ecosystems. However, fewer studies have quantitatively linked wind erosion to detailed grain‐size fractions and associated nutrient content in surface soil and windblown sediment. In this study, we examined (1) the effects of enhanced wind erosion on surface soil particle‐size distribution and (2) carbon (C) and nitrogen (N) characteristics of windblown sediments in a typical desert grassland of southern New Mexico. Our results show that surface soil has become noticeably coarser over a 2‐year period. In particular, content of soil particles in the category of 250–500 μm increased significantly, but soil particles in the fractions of 50–125 μm and <50 μm were significantly depleted. In addition to the enrichment of C and N in the windblown sediments, our results reveal that fine particles (e.g., D < 50 μm) were enriched to a much higher degree at height than C and N. Significantly, our results reveal that nearly 12% of total organic carbon (TOC) and 9% of total nitrogen (TN) were found in the particles with diameter <50 μm, which account for only 1–2% of the mass of windblown sediments. In this wind susceptible environment, our findings suggest that (1) significant soil texture change (e.g., the loss of soil fines) driven by wind erosion could happen rapidly and soil fine particles (e.g., silt and clay) may be depleted within a few years and (2) the loss of even a small fraction of fine particles may indicate a substantial depletion of soil C and N.